ANALYSIS OF THE MAINTECHNOLOGICALPARAMETERS OF THE CONDENSER - Mirzaumidov, Asilbek; Ganikhanov, Khusankhon; Mavlyanov , Aybek; Abdusamatov, Alisher (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article is presented an analysis of the results of the study of the main technological parameters of the existing and improved cotton fiber condenser. The air flow rate and the coefficient of resistance inside the existing and improved condenser are investigated.